Quality management system and firm performance in an emerging economy: The case of Colombian manufacturing industries - prepared for the Institutions for Development Department - Juan Miguel Gallego; Luis H. Gutiérrez Urdaneta (Inter-American Development Bank (IDB), 2017)
Over one million firms around the world have adopted a Quality Management System (QMS) that conforms to ISO 9001 certification in 2015 and recent figures show that certifications have rapidly increased in emerging economies. ISO 9001 is considered a signal of high quality for products or services in markets with large imported competition or firms competing in international markets. However, implementing ISO 9001 certification entails large costs to companies for documentation of operating procedures, training, internal auditing, and corrective action. The impact of QMS on firm performance is unknown in developing economies and is still under-researched for more developed countries. This paper takes advantage of unique data on the status of certified and non-certified manufacturing firms in Colombia (an emerging economy) and matches it with firm performance. In 2006, the Colombian government launched policies to reduce the cost of adopting certification. We use this change to implement a difference-in-differences specification on panel data of certified and non-certified firms by matching samples at the year 2003, three years before the policy change. This is the most comparable data possible. Our findings suggest that firms that adopt ISO 9001 certification increase labor productivity (measured as added value over labor) by 12 percent, and sales per employee and wages by 8 percent. The effect is larger for firms that adopted certifications two years after the new policies compared with firms that adopted them immediately. The potential mechanism to explain gains in firm performance is human capital because, prior to the changes, firms with more temporary workers could not take advantage of certification.
Keywords: L15; D22; O31; 330; ISO 9001; emerging economies; innovation; productivity; quality certification